Status Limnologis Situ Cilala Mengacu pada Kondisi Parameter Fisika, Kimia, dan Biologi Perairan - Niken T.M. Pratiwi; Enan M. Adiwilaga; Johan Basmi; Majariana Krisanti; Oji Hadijah; Pieka Wulandari K. (Universitas Gadjah Mada, 2007)
The purpose of this research was to study the limnological status of Cilala reservoir, based on physical, chemical, and biological parameters. The observation comprised some morphometric of surface and vertical dimension, water quality measurements, plankton community structure, and primary productivity. Based on some morphometric condition, Cilala reservoir has a high potention of biological productivity, but the area of lake begins narrowing. The physical and chemical characteristic showed that Cilala reservoir was still in good condition. The condition of Total Suspended Solid (TSS) at inlet and the water debit of outlet showed that the waters has a relatively high potention of sedimentation that lead to a shallowing condition. There were found 95 genus of phytoplankton from seven classes (Bacillariophyceae, Chlorophyceae, Cyanophyceae, Chrysophyceae, Euglenophyceae, Pyrrophyceae, and Xanthophyceae). It was also found four major groups of zooplankton, i.e. Rotifera, Copepoda, Cladocera, and Protozoa. Although the primary productivity was relatively low, based on orthophosphate, chlorophyll-a, and Nygaard Index, the water was in mesotrophic-eutrophic status. As a whole, Cilala reservoir was still appropriate for fisheries activities.